Assessment of the Effects of Double-Stranded RNAs Corresponding to Multiple Vitellogenesis-Inhibiting Hormone Subtype I Peptides in Subadult Female Whiteleg Shrimp, Litopenaeus vannamei - Kang, Bong Jung; Sultana, Zakea; Wilder, Marcy N. (Frontiers in Endocrinology, 2021)
Vitellogenesis-inhibiting hormone (VIH) negatively regulates reproduction in shrimp and other decapod crustaceans. In order to assess the effects of transcriptional silencing by multiple VIH subtype I sinus gland peptides (SGPs) on ovarian maturation in female whiteleg shrimp, Litopenaeus vannamei, we synthesized five dsRNAs targeting Liv-SGP-A, −B, −C, −F, and −G and injected them into subadults. The following treatments were employed: sgpG-dsRNA (targeting Liv-SGP-G), sgpC-dsRNA (targeting Liv-SGP-C), and mixed-dsRNA (targeting Liv-SGP-A, −B, and −F). The expression of Liv-SGP-G in eyestalks was significantly decreased at 10, 20, and 30 days after the injection of sgpG-dsRNA In addition, it was significantly decreased at 10 and 30 days after the injection of mixed-dsRNA. The expression of vitellogenin (Vg) gene expression in the ovaries, and concentrations of Vg protein in the hemolymph, were not changed by the administration of any dsRNA treatment (the ovaries remained immature in all treated individuals and contained mostly oogonia and previtellogenic oocytes). Although the administration of dsRNAs corresponding to multiple VIHs did not promote ovarian maturation, this is the first report of the co-transcriptional repression of Liv-SGP-G by the injection of dsRNA for homologous genes (Liv-SGP-A, −B, and −F). These results indicate that subadults can respond to the techniques of transcriptional silencing.